2022
DOI: 10.1080/20008198.2022.2046953
|View full text |Cite
|
Sign up to set email alerts
|

Exploring complex-PTSD comorbidity in trauma-exposed Northern Ireland veterans

Abstract: Background Complex posttraumatic stress disorder (CPTSD) describes the results of complex, prolonged, and/or inescapable trauma, and is typified by avoidance, re-experiencing, sense of threat, affect dysregulation, negative self-concept, and interpersonal disturbances. Additionally, CPTSD is highly comorbid with other common psychopathologies. Objectives A study was conducted in a trauma-exposed UK Armed Forces Veteran population resident in Northern Ireland ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Previous studies have already shown that PTSD and CPTSD occur as responses to traumatic life events and that their prevalence was high both in the general population and in clinical samples (e.g., Maercker et al, 2022;Spikol et al, 2022). In addition, it has been shown by different studies that approximately half of the individuals affected by PTSD and CPTSD are also diagnosed with a depressive disorder (Flory & Yehuda, 2015;Karatzias et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already shown that PTSD and CPTSD occur as responses to traumatic life events and that their prevalence was high both in the general population and in clinical samples (e.g., Maercker et al, 2022;Spikol et al, 2022). In addition, it has been shown by different studies that approximately half of the individuals affected by PTSD and CPTSD are also diagnosed with a depressive disorder (Flory & Yehuda, 2015;Karatzias et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature indicates that PTSD and CPTSD are usually comorbid with depression (e.g., Flory & Yehuda, 2015; Spikol et al, 2022). While there are studies that have shown high prevalence rates of PTSD and depression among genocide survivors (e.g., Kayiteshonga et al, 2022; Mutuyimana et al, 2021), these studies have not assessed the rate of comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The ITQ is also a useful tool for tracking clinically significant treatment‐related changes (Bongaerts et al, 2022; Cloitre et al, 2021) among the general population. Spikol et al (2022) reported that veterans experiencing CPTSD were also likely to have histories of repeated/cumulative trauma and report a range of associated psychopathologies. An assessment of the relative mediational roles played by risk factors and cognitive‐emotional mechanisms in the relation between ITQ‐assessed CPTSD and AUD is therefore warranted (Karatzias & Cloitre, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that around 37% of Northern Irish veterans (n = 1,267) met criteria for PTSD [8] which is substantially higher than a general UK population prevalence rate of PTSD of 5% in any previous 12 months [9]. Furthermore, the relatively new diagnostic entity of Complex PTSD (CPTSD), characterised by a high symptom burden, appears particularly common amongst military veterans with studies showing that up to 80% of help-seeking veterans with PTSD also have CPTSD [9,10]. This suggests that veterans with PTSD are a population vulnerable to severe mental ill health and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%